Studies on hydraulics of augmented ground water recharge through recharge shaft - SINGH, PUSHPENDRA KUMAR; VERMA, J. R.; ., JANHAVI; SINHA, JITENDRA; SAHU, R. K. (Journal of Soil and Water Conservation, 2020)
Artificial groundwater recharge is done when the natural recharge becomes inadequate to compensate for the excessive groundwater withdrawal to meet the water requirements of the society. A reliable assessment of artificial recharge is necessary for sustainable groundwater management. A mathematical model has been developed to estimate the rate of groundwater recharge through recharge shaft. The model takes the various dimensions of shaft as well as the hydraulic characteristics of the area. The recharge rate through the shaft has been estimated with and without taking into account the mound formation around the recharge point. For the validation of model, the observed values of rate of recharge through the shaft have been compared with the values predicted by the mathematical model. The percentage difference of predicted recharge over the observed recharge increases when the shaft diameters considered are 1.5 m and 2.0 m for without the mound incorporation while it decreases with shaft diameter of 2.5 m. The percentage difference of predicted over observed with mound incorporation are increasing as the hydraulic head and diameter of recharge shaft increases. The predicted values closely match with observed, with an over estimation of 5.52 - 10.47 percent with the diameter of recharge shaft 2.5 m in case of without mound formation while incorporating mound formation it was 47.67 - 74.75 percent.